DIAGNOSTIC VALUE OF CYTOKINE DYNAMICS IN PHYSIOLOGICAL GESTATION - Turdieva Dilnavoz Olimovna (Web of Journals Publishing, 2025)
Pregnancy represents a unique immunological state characterized by complex, finely tuned changes in the maternal immune system, aimed at maintaining tolerance to the semi-allogeneic fetus while preserving adequate immune defense.